1995
DOI: 10.1007/bf01192989
|View full text |Cite
|
Sign up to set email alerts
|

Selenium content of breast milk

Abstract: Selenium levels in human milk in the winter period ranged from 5.3 micrograms/l to 23.8 micrograms/l, the mean value being 11.0 micrograms/l. The nursing women were divided into several groups according to the results of a questionnaire, i.e. according to their social status (refugees or otherwise), number of deliveries, post partum days, the weight they had gained during pregnancy, their age and smoking habits. The mean levels of selenium for each group are presented. Selenium was determined by hydride genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Maternal age, BMI, iron supplementation, and smoking do not affect breast milk selenium concentrations (165,239,247,250). One study found an inverse correlation between maternal parity and breast milk selenium in late lactation (251), although a similar association was not found in other studies (239,250).…”
Section: Seleniummentioning
confidence: 89%
“…Maternal age, BMI, iron supplementation, and smoking do not affect breast milk selenium concentrations (165,239,247,250). One study found an inverse correlation between maternal parity and breast milk selenium in late lactation (251), although a similar association was not found in other studies (239,250).…”
Section: Seleniummentioning
confidence: 89%
“…With regard to reproductive experience, there were no significant differences in maternal serum Se (Kumpulainen et al 1985) or in breast-milk Se (Mandic et al 1995) due to parity status. Indeed, Arnaud et al (1993a ) found no significant correlation between milk Se with parity or maternal age (Grandjean et al 1995).…”
Section: Maternal Constitutional Factorsmentioning
confidence: 97%
“…However, Funk et al (1990) found an inverse correlation between parity and milk Se only in late lactation. Although there is a significant correlation between Se status (toenail Se) and smoking (Virtanen et al 1996), there was no significant difference in milk Se between smoking and non-smoking mothers (Mandic et al 1995).…”
Section: Maternal Constitutional Factorsmentioning
confidence: 99%
“…3). Some researchers did not also find statistically significant correlation between dietary selenium and milk selenium values [13] but some investigators found selenium concentration in breast milk to be closely related to dietary selenium intake [32][33][34].…”
Section: Seleniummentioning
confidence: 99%
“…Mineral concentrations in human milk generally do not correlate well with maternal intake, with the exception of selenium and iodine [10]. Some investigators report a positive correlation between dietary intake of selenium and iodine and the concentration of these trace elements in maternal milk [11,12], while others have been unable to demonstrate such a relationship [13]. Since there is no nutritional data available about the dietary intake of trace elements and their relationships to maternal milk composition of lactating mothers in Rio Grande Valley, this study was conducted to find relationships between estimated dietary intake of zinc, iron, selenium, and iodine and concentration of these elements in the maternal milk of lactating mothers.…”
Section: Introductionmentioning
confidence: 98%